A Research Method of IGBT Non Stationary Mode for Power and Electrical Equipment Control - Lu, Zhiyu; Popov, Maksim G.; Zakharova, Elena V.; Gushin, Mikhail V.; Paschoareli, Dionizio [UNESP] (IOS Press, 2022)
The non-stationary mode characteristics of the generalized power equipment numerical experiments are analyzed, and the electrophysical dynamic characteristics and reliability of the IGBT in the power conversion process are studied. Based on the results of short-circuit numerical experiments and the steady-state mode of pulse width control, this paper introduces a method for analyzing the nonlinear dynamic process of IGBT drive modules during power conversion. The structure of a software algorithm for conducting numerical experiments to study the non-stationary operation mode of asynchronous electromechanical machines is proposed, and the numerical solution of transient nonlinear differential-algebraic equations of electrical equipment is described by gradient parameter method. The results of this study will help to study the dynamic nonlinear characteristics of the operation process of power and electrical equipment control and automation tools, and have practical significance for evaluating the computational efficiency and reliability of developing mathematical models in the next research work.
Keywords: dynamic; emergency; IGBT; non-stationary; nonlinear differential equations; nonlinearity; power conversion; power electrical equipment; reliability